The analysis of physical conditions of Puslatkot athletes of Kediri city for "Kediri Emas" in porprov 2019 - Herpandika, Reo Prasetiyo; Yuliawan, Dhedhy; Rizky, Muhammad Yanuar (Jurnal SPORTIF : Jurnal Penelitian Pembelajaran, 2019)
This study based on the problems that occurred in the Training Center (Puslatkot) of Kediri City in preparing the athletes for East Java Province Sports Week (Porprov) 2019. Lack of data on the athletes' physical condition became an important issue in implementing the training programs, besides, the condition of the athletes which was poorly monitored caused the progression of the practice principle that would not be applied. This study aimed at finding out the athletes' physical condition which became a basis for trainers' evaluation in determining the training program. This study used descriptive quantitative research methods in which the survey was as a research approach. The instrument used was a physical condition test created by a team from UN PGRI Kediri with 54 athletes as research samples chosen by using a random sampling technique. The results of the study of the overall physical condition of Puslatkot athletes showed that 28% was in the excellent criteria, 31% was in the good criteria, 17% was in the medium criteria, 24% was in the poor criteria, and 0% was in the very poor criteria. It could be concluded that the physical condition of Puslatkot athletes of Kediri City was included in the good criteria with a percentage of 31%.